The effectiveness of combined anaerob - aerob biofilters and phytoremediation using Pistia stratiotes for reducing TSS and Ammonia content in sago industrial liquid waste - Evi Iskana Manurung; Sampe Harahap; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The sago industrial liquid waste is rich in TSS and ammonia and thus need to be processed before being flown to environment. A study aims to reduce the TSS and ammonia in that waste has been conducted in January - April 2017. The sago liquid waste (135 liter) was kept in an anaerob tank (with gravel, sand and palm fiber media) for 10 days. The waste was then flown to an aerobic tank (with charcoal and palm fiber media) for 5 days and finally the waste was treated in a phytoremediation pond that was completed by Pistia stratiotes for 15 days. By the end of the experiment, the TSS reduced from 376 mg/L to 30 mg/L (the effectivity was 88.84% - 92.02%), while the ammonia reduced from 11.82 mg/L to 0.01 mg/L (the effectivity was 48.48% - 99.7%). Other water quality parameters such as pH and DO were improved. The treated waste was used for rearing Cyprinus carpio fingerlings for 7 days and survival rate of the fish was 93%. Based on data obtained, it can be concluded that the combination of anaerob-aerob biofilters and phytoremediation using P. stratiotes is effective to reduce the TSS and ammonia content in the sago industrial liquid waste.Keyword: TSS, Ammonia, Biofilters, Pistia stratiotes